The impact of Loa loa microfilaraemia on research subject retention during a whole sporozoite malaria vaccine trial in Equatorial Guinea. (8th April 2022) - Manock, Stephen R; Nsue, Vicente Urbano; Olotu, Ally; Mpina, Maximillian; Nyakarungu, Elizabeth; Raso, José; Mtoro, Ali; Ondo Mangue, Martín Eka; Ntutumu Pasialo, Beltrán Ekua; Nguema, Rufino; Riyahi, Pouria; Schindler, Tobias; et al.
Abstract: Loa loa microfilariae were found on thick blood smears (TBSs) from 8 of 300 (2.7%) residents of Bioko Island, Equatorial Guinea, during a Plasmodium falciparum sporozoite malaria vaccine clinical trial. Only one subject was found to have microfilaraemia on his first exam; parasites were not discovered in the other seven until subsequent TBSs were performed, at times many weeks into the study. All infected individuals were asymptomatic, and were offered treatment with diethylcarbamazine, per national guidelines. L. loa microfilaraemia complicated the enrolment or continued participation of these eight trial subjects, and only one was able to complete all study procedures. If ruling out loiasis is deemed to be important during clinical trials, tests that are more sensitive than TBSs should be performed.